2009
DOI: 10.14411/fp.2009.019
|View full text |Cite
|
Sign up to set email alerts
|

Coccidia of rabbit: a review

Abstract: Abstract:This article summarises the current knowledge of the rabbit coccidia and the disease they cause. Various aspects, such as life cycles, localisation in the host, pathology and pathogenicity, immunity and control, are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
166
0
12

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(181 citation statements)
references
References 89 publications
3
166
0
12
Order By: Relevance
“…Gross hepatic changes associated with coccidial lesions in the present study on the kiwi are typical of those seen in hepatic coccidial infections in other avian and mammalian host species (Critchley et al, 1986;Reece, 1989;Dai et al, 1991;Canfield & Hartley, 1992;Pakandl, 2009;O'Brien et al, 2011;Wessels et al, 2011). Most reports of hepatobiliary coccidiosis in other host species, including the magpie-lark and experimentally immunosuppressed chickens, occurred within the biliary duct epithelium (Clark, 1970;Long, 1970Long, , 1971Lee & Long, 1972;Levine & Ivens, 1972;Collins et al, 1988;Reece, 1989;Dai et al, 1991;Brunnert et al, 1992;Schafer et al, 1995;Williams et al, 1996;Pakandl, 2009). Lesions within hepatic tissue outside the biliary system have not been described previously in natural infections of any avian species, although they have been reported in wallabies and in a single goat (Canfield & Hartley, 1992;Mahmoud et al, 1994).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Gross hepatic changes associated with coccidial lesions in the present study on the kiwi are typical of those seen in hepatic coccidial infections in other avian and mammalian host species (Critchley et al, 1986;Reece, 1989;Dai et al, 1991;Canfield & Hartley, 1992;Pakandl, 2009;O'Brien et al, 2011;Wessels et al, 2011). Most reports of hepatobiliary coccidiosis in other host species, including the magpie-lark and experimentally immunosuppressed chickens, occurred within the biliary duct epithelium (Clark, 1970;Long, 1970Long, , 1971Lee & Long, 1972;Levine & Ivens, 1972;Collins et al, 1988;Reece, 1989;Dai et al, 1991;Brunnert et al, 1992;Schafer et al, 1995;Williams et al, 1996;Pakandl, 2009). Lesions within hepatic tissue outside the biliary system have not been described previously in natural infections of any avian species, although they have been reported in wallabies and in a single goat (Canfield & Hartley, 1992;Mahmoud et al, 1994).…”
Section: Discussionsupporting
confidence: 64%
“…The route of migration in other hepatic species of coccidia is unclear; however, both lymphatic and haematogenous spread have been implicated (Smetana, 1933;Horton, 1967;Pakandl, 2009). Asexual and sexual stages of E. reichenowi and E. gruis in cranes occur primarily in macrophages, and it is suggested that these species use this route to penetrate into the blood and/or lymphatic system (Novilla et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Eimeria oryctolagi (Pakandl, 2009). Following the infection of Eimeria sp anorexia, abdominal swelling, diarrhea and weight loss usually occurs, but the specific clinical sign for E. stiedai infection are liver swelling, bile duct widened, jaundice and persistence of white nodules in various sizes on the liver surface which containing viscous fluid and oocysts (Al-Rukibat et al, 2001;Al-Mathal, 2008).…”
Section: Eimeria Magna Eimeria Perforans Eimeria Media Eimeria Irrmentioning
confidence: 99%
“…However, the regular use may cause parasite resistance, additionally medicine residue in meat also need to be in attention concerning to consumer health disorder. Live vaccines are another method for controlling coccidiosis in domestic poultry (Pakandl, 2009;Price, 2012;Chapman and Jeffers, 2014). Nevertheless, the use of this vaccine has not been fully accepted, partly because of economic reasons, the side effects during early treatment and this vaccine only give temporary protective immunity (Williams, 2002), moreover the use of live vaccines should be followed by maintenance and good health in order to enhance the vaccine function optimally (Yang et al, 2012).…”
Section: Eimeria Magna Eimeria Perforans Eimeria Media Eimeria Irrmentioning
confidence: 99%
“…Ten of these develop in the intestines, the exception being E. stiedai (Lindemann 1865) Kisskalt and Hartmann, 1907 which is the only liver coccidium infecting the epithelium of bile ducts. Eimeria stiedai is considered to be one of the most important rabbit coccidia (Yakhchali and Tehrani 2007) together with the intestinal species, E. intestinalis and E. irresidua (Pakandl 2009). Experimental infections with E. stiedai can result in severe functional disorders and death (Hein and Lämmler 1978;Arnoni 1979, 1981).…”
mentioning
confidence: 99%